Natural products for treating bone diseases by targeting ferroptosis and promoting regeneration: A narrative review - Chuanxin Wang; Bingyang Yan; Wenfei Wu; Di Luo; Haisheng Yu; Duanrui Liu; Wenzhao Wang; Liang Ma (Regenerative Medicine Reports, 2026)
Ferroptosis, an iron-dependent form of programmed cell death driven by lipid peroxidation, plays a critical dual role in the pathogenesis and treatment of bone diseases. While it can be therapeutically harnessed to eliminate malignant cells in osteosarcoma, its aberrant activation contributes to the degeneration of bone and cartilage in osteoporosis, osteoarthritis, and intervertebral disc degeneration, thereby severely impairing the intrinsic regenerative and repair capacity of musculoskeletal tissues. A significant challenge is the precise modulation of ferroptosis to concurrently inhibit pathological cell death and activate regenerative and protective processes. This review systematically elucidates the therapeutic potential of natural products in treating these bone diseases by targeting ferroptosis, with a dedicated focus on their emerging role in promoting tissue regeneration and repair. We report that a spectrum of natural compounds, such as icariin, astragaloside IV, and baicalein, not only inhibits ferroptosis in osteoblasts, chondrocytes, and nucleus pulposus cells—exacerbating a cytoprotective effect—but also actively promotes a conducive microenvironment for regeneration. These benefits are mediated through the modulation of key pathways, including the Nrf2/HO-1 axis, glutathione peroxidase 4 restoration, and System Xc – , which collectively reduce oxidative stress, restore cellular homeostasis, and enhance the function of bone marrow mesenchymal stem cells and progenitor cells. Despite this promise, key issues persist, including the cell type-specific effects of ferroptosis modulators, the complex crosstalk between ferroptosis and other cell death or inflammatory pathways, and the poor bioavailability of many natural agents. This regenerative potential is closely linked to the resolution of ferroptosis-associated inflammation and oxidative damage, allowing progenitor cells to proliferate and differentiate. In conclusion, targeting ferroptosis with natural products represents a promising regenerative medicine strategy that connects the inhibition of pathological degeneration with the stimulation of bone and cartilage repair. The multi-target and tissue-protective nature of these compounds offer significant clinical potential. Future research should prioritize the development of advanced delivery systems (e.g., nanoparticle-based), the integration of network pharmacology and multi-omics approaches for target discovery, and the validation of these regenerative outcomes in sophisticated 3D disease models and clinical trials.